2000
DOI: 10.1002/(sici)1438-9312(200004)102:4<287::aid-ejlt287>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Production of specific-structured triacylglycerols by lipase-catalyzed reactions: a review

Abstract: Regiospecificity is one of the major advantages of using lipase technology for the modification of oils and fats to produce high‐value added products, such as cocoa butter equivalents, human milk fat substitutes, and other specific‐structured lipids. Due to the high cost of biocatalysts, the mainstream applications of lipases for normal oils and fats are still limited. Therefore, positional specificity of lipases has the priority and will be the target property to be exploited for commercial and industrial dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
7

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(84 citation statements)
references
References 117 publications
1
76
0
7
Order By: Relevance
“…The industrial transesterification process is currently performed by chemical means, using high temperatures and alkaline metals as the reaction catalyst (Ribeiro et al, 2009). In the enzymatic process, lipases can be used as biocatalysts to promote the exchange of triacylglycerols, showing greater efficiency and leaving no residues (Xu, 2000). However, several studies have indicated that such processes are very expensive due to the high cost of purifying the microbial enzymes (de Castro et al, 2004;Noor et al, 2003).…”
Section: Brazilian Journal Of Chemical Engineeringmentioning
confidence: 99%
“…The industrial transesterification process is currently performed by chemical means, using high temperatures and alkaline metals as the reaction catalyst (Ribeiro et al, 2009). In the enzymatic process, lipases can be used as biocatalysts to promote the exchange of triacylglycerols, showing greater efficiency and leaving no residues (Xu, 2000). However, several studies have indicated that such processes are very expensive due to the high cost of purifying the microbial enzymes (de Castro et al, 2004;Noor et al, 2003).…”
Section: Brazilian Journal Of Chemical Engineeringmentioning
confidence: 99%
“…Among the currently available methods for modifying lipids, lipase-catalyzed reactions are better than conventional chemical methods since lipases mimic natural pathways, which concern mild reaction conditions, high catalytic efficiency, and the inherent selectivity of natural biocatalysts. Although lipase-catalyzed reactions have been widely studied as useful tools for modification of plant and fish oils in recent years (SENANAYAKE;SHAHIDI, 1999SHAHIDI, , 2002XU et al, 2000;PAEZ et al, 2002), related available studies on animal fats, especially lard, are few although some do exist for butterfat MALCATA, 2002;1998;1997;SAHIN;AKOH;KARAALI, 2005;NIELSEN et al, 2006). Typical applications of lipase-catalyzed interesterification reactions include the production of cocoa butter substitutes, human milk fat substitutes, partial acylglycerols, modified fish oil products, margarines, structured lipids, and several lipid products (SAHIN; AKOH; KARAALI, 2005;NIELSEN et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Commercial lipases are available from microbial, plant, and animal sources. Among those, microbial lipases are the most attractive ones and their utilization has been described extensively (XU, 2000;BALCÃO et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Milk and milk products enriched in oleic acid or PUFA exist in the market, but those are produced merely by blending with vegetable or Wsh oil concentrates. Lipase-catalyzed production of nutritionally improved oils and fats at industrial scale is limited to the production of structured lipids of vegetable origin, namely the human milk substitute Betapol®, cocoa butter replacers, and diacylglycerol-based oils [36][37][38]. The relatively high cost of speciWc lipases is still one of the major impediments for the development of such processes.…”
Section: Milk Fat Engineeringmentioning
confidence: 99%
“…Structured acylglycerols contain certain fatty acids in speciWc positions of the glycerol molecule, which gives them special nutritional properties. The short-chain fatty acid fraction of milk fat can be used for the synthesis of medium-chain triacylglycerols (indicated for parenteral and sports nutrition), low-caloric fats (triacylglycerols containing at least one short-and one long-chain fatty acid) [37], and short-chain sucrose polyesters to be used as fat substitutes [41]. Short-chain fatty acids for the synthesis of SL are currently obtained from coconut oil fractions containing C8-C10 fatty acids or synthetically.…”
Section: Mono-and Diglyceridesmentioning
confidence: 99%